Koncepcja patriotyzmu krytycznego jako punkt odniesienia polskiej polityki historycznej - Katarzyna Głowacka (Politeja)
THE CONCEPT OF „CRITICAL PATRIOTISM” AS A BENCHMARK FOR POLISH POLITICS OF MEMORY: PARLIAMENTARY DISCOURSE ON THE KATYN MASSACRES AND THE GENOCIDE IN VOLHYNIA